The world news prism : challenges of digital communication - Hachten, William A.; Scotton, James Francis, 1932- (Chichester, West Sussex : Wiley-Blackwell, 2012)
'The World News Prism enjoys a well-earned reputation for excellence in its in-depth analysis of the changing role of transnational news media in the 21st-century. In the eighth edition of this classic text, the authors expand their discussion of news systems in developing nations and the impact of digital media on traditional societies. A new chapter dedicated to evolving media in Egypt, Tunisia, and elsewhere in Africa and the Middle East explores the role of the Internet, cell phones, and Al Jazeera in facilitating momentous political change in the region. The book also provides important updates on the decline of print media in the West and the challenges this poses to global reporting now and for the future. Combining scholarly insights with a concise and accessible writing style, The World News Prism: Challenges of Digital Communication lends remarkable clarity to the fog of today's global information revolution'--
Includes bibliographical references and index.
Keywords: Foreign news; Communication, International; Journalism -- Political aspects; Digital media; Mass media and globalization